An overview of greenhouse gases emissions in Hungary. (10th September 2021) - Mohammed, Safwan; Gill, Abid Rashid; Alsafadi, Karam; Hijazi, Omar; Yadav, Krishna Kumar; Hasan, Mohd Abul; Khan, Afzal Husain; Islam, Saiful; Cabral-Pinto, Marina M.S.; Harsanyi, Endre
Abstract: In Hungary, successive steps have been taken toward adjusting GHG emissions from all sectors on a national scale. However, few studies were carried out to analyze the environmental dimensions of GHG emissions from an economic point of view. In this research, the contemporary changes of GHG emissions between 1985 and 2018 were analyzed using the Mann-Kendall test (M-K test); along with the interaction between GHG emissions and economic growth by applying the environmental Kuznets curve (EKC). Results showed that the industrial sector has been the main source of CO2 -emitting, and contributed 72% of the total emissions. Meanwhile, the biggest CH4 -emitting sector was the waste sector (44%), followed by the agricultural sector (39%). Nonetheless, the agricultural sector was responsible for more than 65% of N2 O emissions over Hungary. The M-K test results showed that total CO2 emissions were reduced significantly ( p < 0.05) by −1001 thousand tonnes/year. Similarly, the total N2 O emissions were subject to a significant decrease ( p < 0.05) of −0.31 thousand tonnes/year. Interestingly, the long-run positive significant coefficient on income growth (GDP), and negative significance on (GDP) 2 indicate EKC's existence for CO2 emission, CH4, and N2 O in Hungary, revealing that GHG emissions will increase at a decreasing rate with economic growth in Hungary. The output of this research is useful for decision-makers to consider the environmental dimensions of GHG emissions and set priorities for minimizing emissions by sectors. Graphical abstract: Image 1 Highlights: This research is the first attempt to evaluate the interaction between Hungarian income and GHG emissions, through EKC. In Hungary, the energy sector is the highest CO2 -emitting sector (34%), followed by the industrial sector (22%). The total emission of CO2, CH4, and N2 O witnessed a significant (p<0.05) negative trend between 1985 and 2018. The study reports an EKC transition in Hungary, due to the implementation of national environmental policies. The economic growth in the future would lead to environmental improvement.